Validating an implicit cognition battery in Parkinson’s disease and assessing its sensitivity to pharmacological manipulation - Nahon, S (2019)
Introduction: Cognitive decline is one the most common and debilitating non-motor symptoms associated with Parkinson’s disease. Currently, no treatment options exist for cognitive impairment in PD, partly due to the lack of measurement tools sensitive to the subtle early cognitive changes and pro-cognitive pharmacological manipulation in the disease. Implicit cognition shows promise in detecting these otherwise overlooked changes.